Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian Mobil Suzuki Ertiga Pada PT Samekarindo Indah Samarinda - dewi, tutut surya (EKONOMIA, 2013)
The influence of brand awareness toward purchasing decisions of Ertiga Car in PT Samekarindo Indah Samarinda. The purpose of this research is to investigate the influence of brand awareness, perceived quality, brand association, and brand loyalty toward purchasing decisions. This research was conducted on the consumer or the owner of Suzuki Ertiga Car in PT Samekarindo Indah Samarinda, and the number of samples are determined 100 respondents using accidental sampling method. The analytical method used is the quantitative.. Where (Y) is the purchase decision variables, (X1) is brand awareness, (X2) is perceived quality, (X3) is brand association, and (X4) is brand loyalty. Hypothesis testing using the t-test indicates that the four independent variable found to influence the purchase dependent variable, then using F-test can be known that the four variable are well deserved to test the purchase decision dependent variable. The Adjusted R Square value 0.538 showed that 53,8% of purchase decision variation can be explained by the four independent variables in the regression equation, while the rest of 46.2% is explained by other variables outside of the four variables used in this study Â